The Influence of the Good Corporate Governance of the Company on the Company's Property and Real Estate In BEI - Istikoma Ulva, Siti Nurlaela & Kartika Hendra Titisari (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
The purpose of this study is to conduct empirical test on influence of goodcorporate governance of the company on the company's property and real estate inIndonesia stock exchange years 2014-2016. The difference with previous researchlocated on the use of independent variable and the dependent variable. The data inthis study is secondary data obtained from the Indonesia stock exchange. Thenumber of sample as many as 21 of the company's property and real estate 2014-2016 period, using the method of purposive sampling. Analytical techniques usedto use multiple linear regression, data processed using the SPSS 17. The results ofthe test showed that the variables are independent Commissioners and Board ofDirectors to the company's value, while the audit committee has no effectsignificantly to the value of the company.Keywords: good corporate governance, firm value